2009
DOI: 10.1158/0008-5472.can-08-3022
|View full text |Cite
|
Sign up to set email alerts
|

NKX3.1 Activates Expression of Insulin-like Growth Factor Binding Protein-3 to Mediate Insulin-like Growth Factor-I Signaling and Cell Proliferation

Abstract: NKX3.1 is a homeobox gene that codes for a haploinsufficient prostate cancer tumor suppressor. NKX3.1 protein levels are down regulated in the majority of primary prostate cancer tissues. NKX3.1 expression in PC-3 cells increased IGFBP-3 mRNA expression 10-fold as determined by expression microarray analysis. In both stably and transiently transfected PC-3 cells and in LNCaP cells NKX3.1 expression increased IGFBP-3 mRNA and protein expression. In prostates of Nkx3.1 gene-targeted mice Igfbp-3 mRNA levels corr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…4 In early human prostate cancer we have found that NKX3.1 expression is down-regulated over a broad range 4,24 NKX3.1 is known to have a broad effect on transcriptional targets, both increasing and decreasing expression of many genes. 21,25 However, our experiments with reporter constructs containing the cognate NKX3.1 DNA binding sequence have shown that promoter binding by NKX3.1 fails to activate transcription directly and only was observed to down-regulate gene expression. 26 NKX3.1 is able to cooperate with other transcription factors such as serum response factor to function as a coactivator and enhance transcription.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…4 In early human prostate cancer we have found that NKX3.1 expression is down-regulated over a broad range 4,24 NKX3.1 is known to have a broad effect on transcriptional targets, both increasing and decreasing expression of many genes. 21,25 However, our experiments with reporter constructs containing the cognate NKX3.1 DNA binding sequence have shown that promoter binding by NKX3.1 fails to activate transcription directly and only was observed to down-regulate gene expression. 26 NKX3.1 is able to cooperate with other transcription factors such as serum response factor to function as a coactivator and enhance transcription.…”
Section: Discussionmentioning
confidence: 95%
“…The effect of NKX3.1 on IGFR-I activation was not seen when Long R-IGF-I, an IGFR-I ligand that does not bind to IGFBP-3 was used, or when cells were pretreated with IGFBP-3 siRNA. 21 In contrast, neither NKX3.1(R52C) nor NKX3.1(S48A) had an effect on IGFR-I signaling ( Fig. 2A and B).…”
Section: Effect Of Nkx31(r52c) On Igfbp-3 Expression and Igf-ir Actimentioning
confidence: 88%
See 3 more Smart Citations